Biophilic design elements preferences among government officers in Putrajaya, Malaysia - Abdul Munir, Fadhlizil Fariz; Sapian, Abdul Razak; Zulkifli, Nabilah Huda; Mansor, Mazlina; Ibrahim, Putri Haryati (Malaysian Institute of Planners, 2024)
The theory of human dependence on other living things and their processes is called the “biophilia hypothesis”, and has been discussed in various literature. The theory was then translated into design features, namely "biophilic design", to be assimilated with the built environment, including residential areas, the medical sector and commercial property such as office buildings. Through the implementation of biophilic design in office buildings, the building occupants can improve their physiological and psychological well-being as they spend a lot of time at work. The study examines the selected government office buildings in 00Putrajaya to identify the preferred biophilic design elements among government office workers that can be used to reduce their stress, and thus improve their productivity. Based on the questionnaire survey that was answered by 977 respondents from different types of work schemes, different working space environments, and different employment periods among the government office workers in Putrajaya, the findings have revealed that natural ventilation, external view to nature, and daylighting are the most preferred biophilic design elements that can help them feel less stressed in the office working spaces; these are followed by attraction and beauty, prospect and refuge.